Cellular and molecular basis of IR3535 perception in Drosophila. Issue 2 (9th November 2021) - Shrestha, Bhanu; Nhuchhen Pradhan, Roshani; Nath, Dharmendra Kumar; Lee, Youngseok
Abstract: BACKGROUND: IR3535 is among the most widely used synthetic insect repellents, particularly for the mitigation of mosquito‐borne diseases such as malaria, yellow fever, dengue and Zika, as well as to control flies, ticks, fleas, lice and mites. These insects are well‐known vectors of deadly diseases that affect humans, livestock and crops. Moreover, global warming could increase the populations of these vectors. RESULTS: Here, we performed IR3535 dose–response analyses on Drosophila melanogaster, a well‐known insect model organism, using electrophysiology and binary food choice assays. Our findings indicated that bitter‐sensing gustatory receptor neurons (GRNs) are indispensable to detect IR3535. Further, potential candidate gustatory receptors were screened, among which GR47a was identified as a key molecular sensor. IR3535 concentrations in the range 0.1–0.4% affected larval development and mortality. In addition, N, N ‐diethyl‐ m ‐toluamide (DEET, another commonly used insecticide) was found to exert synergistic effects when co‐administered with IR3535. CONCLUSION: Our findings confirmed that IR3535 directly activates bitter‐sensing GRNs, which are mediated by GR47a. This relatively safe and highly potent insecticide can be largely used in combination with DEET to increase its efficiency to protect livestock and crops. Collectively, our findings suggest that the molecular sensors elucidated herein could be used as targets for the development of alternative insecticides. © 2021 Society of Chemical Industry. Abstract : IR3535 is the most effective insecticide with safety records. In Drosophila melanogaster, it is directly detected as a bitter compound through bitter‐sensing gustatory receptor neurons. GR47a is indispensable for its perception. Furthermore, IR3535 can inhibit sugar responses. These dual mechanisms of IR3535 are major modes of actions as antifeedant.